Prevalensi dan faktor penyebab obesitas pada remaja di Wilayah Jakarta Barat - Laras Sitoayu; Widya Musliha; Prita Dhyani Swamilaksita; Vitria Melani (MEDIA ILMU KESEHATAN, 2021)
Background: Exercise habits, body image, and stress are factors that influence obesity. Obesity is a condition of a person who has a body weight that is heavier than his ideal weight due to the accumulation of fat in his body. Currently, obesity is not only experienced by adults, but also experienced by many teenagers.Objective: This study aims to determine the relationship between exercise habits, body image, and stress with obesity in adolescents.Methods: This study used a cross-sectional research design, which was conducted in SMPN 75 Jakarta and SMPN 229 Jakarta with a sample of 97 people. Data analysis in this study using Chi-Square.Results: From the results of statistical tests showed that there was a relationship between exercise habits, body image, and stress with obesity in adolescents (p 0.05).Conclusion: Adolescents need to carry out anthropometric measurements regularly to determine their nutritional status so that they can control their nutritional status, besides those adolescents must also exercise regularly, avoid stress, and have a positive body image perception to prevent obesity, which can endanger health.